Islamic Law Perspectives on Dumping Practices : A Critical Review - Bahrul Ulum (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Dumping, characterized by selling goods at below-market prices in export markets, poses significant ethical and economic concerns in global trade. Islamic law (shariah), with its emphasis on justice, equity, and harm reduction, provides a unique lens for analyzing such practices. This review synthesizes insights from scholarly works to explore the compatibility of Islamic legal principles with anti-dumping measures. Key findings include Islamic jurisprudence’s proactive stance against predatory pricing (siyasah al-ighraq) for its potential to harm market stability and marginalize smaller producers. Studies show that Islamic law prioritizes public welfare (maslahah) and promotes ethical market behaviors, offering alternative regulatory perspectives to address trade malpractice. Through case studies like Indonesia’s WTO defense on paper dumping and comparative analyses with Saudi trade laws, this review highlights the robust ethical foundation Islamic law brings to contemporary international trade debates. The synthesis concludes by advocating integrative frameworks to harmonize Islamic ethics with global trade governance.